Recruitment and Retention of Rural Health Professionals in Minnesota - MacDougall, Hannah; Woldegerima, Selam; Henning‐Smith, Carrie; Fritsma, Teri; Olson, Andrew P. J. (Health services research, 2025)
ABSTRACT Objective To qualitatively explore the reasons health professionals decide to practice in rural areas. Study Setting and Design Exploratory, cross‐sectional, semi‐structured qualitative interview and focus group study using thematic analysis with a convenience sample of health professionals in rural Minnesota. Interviews and focus groups were conducted virtually and in person, respectively, between August 2023 and March 2024. Data Sources and Analytic Sample Primary interview and focus group data were collected from 19 individual interviews and 3 focus groups (n = 16) with health professionals in rural Minnesota. Interview and focus group recordings were transcribed, deductively coded, and analyzed using constant comparison. Principal Findings Rural health professionals cited autonomy and breadth of practice and patient connection as rewarding and challenging components of practice that were distinctly rural. Barriers to recruitment and retention of rural health professionals included lack of housing (especially rental and short‐term) and accessible childcare. Potentially promising considerations when recruiting and retaining health professionals include loan forgiveness programs, the appeal of increasing racial and ethnic diversity in rural areas, and the ease of community health advocacy efforts. Conclusion Our findings suggest that to recruit and retain rural health professionals, stakeholders could highlight autonomy and patient connection, reduce childcare and housing barriers, and explore community strengths such as racial/ethnic diversity and opportunities for advocacy.